2007
DOI: 10.1186/1472-6920-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity, sources of stress and coping strategies among undergraduate medical students of Nepal

Abstract: Background: In recent years there has been a growing appreciation of the issues of quality of life and stresses involved medical training as this may affect their learning and academic performance. However, such studies are lacking in medical schools of Nepal. Therefore, we carried out this study to assess the prevalence of psychological morbidity, sources and severity of stress and coping strategies among medical students in our integrated problem-stimulated undergraduate medical curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
432
15
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(517 citation statements)
references
References 26 publications
54
432
15
16
Order By: Relevance
“…(15) But this finding of our study is much higher than the prevalence of mental health problems in Dubai medical students found by Ahmadi et al (16) The prevalence of mental morbidity was also higher among our participants compared with Turkish and Nepalese medical students, which are 48% and 20.9% respectively. (21,22) We found higher percentage of abnormal mental health status among our participants in comparison to a study conducted in Tehran University of Medical Sciences, which was 43.9%. (18) However, this difference between Shiraz and Tehran medical students' mental health status cannot be due to the difference between universities' educational curriculums; as medical educational programs are quite consistent in all the universities of Iran.…”
Section: Discussioncontrasting
confidence: 47%
“…(15) But this finding of our study is much higher than the prevalence of mental health problems in Dubai medical students found by Ahmadi et al (16) The prevalence of mental morbidity was also higher among our participants compared with Turkish and Nepalese medical students, which are 48% and 20.9% respectively. (21,22) We found higher percentage of abnormal mental health status among our participants in comparison to a study conducted in Tehran University of Medical Sciences, which was 43.9%. (18) However, this difference between Shiraz and Tehran medical students' mental health status cannot be due to the difference between universities' educational curriculums; as medical educational programs are quite consistent in all the universities of Iran.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous study of Steptoe et al also showed that Asian countries had the highest incidence of depression as compared to other countries [18]. However, this percentage is quite high as compared to the findings of Sreeramareddy et al (20%) and Chan DW (21%) [19,20]. Besides academic pressure and changing environment at college, the high percentage of the study population having depression could be related to social and cultural factors existing in the society.…”
Section: Discussioncontrasting
confidence: 53%
“…However, all persons experience stressful situations differently, and there may not always be a negative reaction associated with the stressful situation 4 . If one views an event or situation as a challenge, it is more likely that a positive outcome will be achieved, whereas, if the situation was viewed as a burden or threat, it is more likely that a negative outcome will be reached , Nepal 9 and Zimbabwe 2 provide evidence that tertiary education is highly stressful and that tertiary students face stressful demands in their student life. It has also been widely reported that health science students are exposed to and experience high levels of stress 6,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Personal stressors experienced by students are well documented 1,2,7,8,9,10,11,12 and include physical problems or impairments, family difficulties, financial difficulties, access to resources, social issues, managing relationships and transitioning through adolescence to adulthood. Academic stressors experienced by students include high academic expectations, rigorous class schedules, integration of classroom and clinical learning, tests and examinations, the amount of class work and poor grades, time management, clinical fieldwork, relationships with supervisors, amongst others 8,13,14,15,16 .…”
Section: Literature Reviewmentioning
confidence: 99%